Modificação de matrizes em análise espectroscópica por Raman e infravermelho médio - Moreira, Walace Martins (Universidade Federal de São Carlos, 2021)
The spectroscopy methods of analysis, as Mid Infrared (MIR) and Raman spectroscopy, are based on the interaction of light and matter. These techniques present advantages, such as, non-destructive analysis, low cost and little or no sample preparation. However, in the analysis of complex matrices (food, beverages, and drugs), interferents agents decrease the capacity of these techniques, especially in detecting of minority compounds. In this way, the modification of these matrices in order to reduce the interferences, presents itself as a viable alternative, expanding the analysis capacity and enabling new applications of such techniques. In this work, it was performed the modification of matrices in three different applications for analyses using MIR and Raman spectroscopy. The aim of carrying out the treatment of samples before the analysis aimed to overcome limitations of analytical techniques related to direct analysis, such as fluorescence in Raman and water interference in mid-infrared. In the first application, it was proposed the quantitative determination and stability study of acetylsalicylic acid (ASA) in commercial samples by Raman spectroscopy and univariate analysis. For this purpose, four solution of 3% m/v AAS at pH values varying from 6 to 12 were prepared. Raman spectra were collected at intervals of 30 min in the first two hours of analysis and 1 h of interval after two hours, in a total of 8 hours. For quantitative determination, a concentration calibration curve in the range of 1 to 5% m/v of AAS, was built. After evaluating of stability, two commercial drugs containing AAS were purchased in the local market and the content of the active ingredient was determined. The values found by Raman Spectroscopy were compared with the results obtained by the standard method (HPLC) and presented relative deviation below 1%. In the second application, a sample opening method was proposed using liquid-liquid partition with ethyl acetate to analyze by FTIR-ATR 11 brands of Pilsner beers, divided into the Standard American Lager and Premium American Lager categories. The data were pre-processed the exploratory study performed using Principal Component Analysis (PCA). According to the results, spectral patterns (fingerprints) of the compounds present in the organic extract of the analyzed samples were obtained. It was possible to verify that FTIR-ATR technique was able to separate the analyzed beer brands in distinct groups. Moreover, the FTIR-ATR was able to separate samples of different brands according to the production location. Finally, in the third application the quantitative analysis of ethanol in beer, wine and whiskey samples was performed by Raman Spectroscopy. As a strategy to reduce interferents, the modification of the matrices with sodium hypochlorite was carried out. This method has as its main objective to suppress the fluorescence of samples, caused by the components present in these matrices. The results showed that the use of sodium hypochlorite was effective in the suppressing of fluorescence, allowing for the quantitative analysis of ethanol in the analyzed matrices. The relative deviation between Raman Spectroscopy and the reference method (Gas Chromatography - GC) was below10%.
Modification of matrices in spectroscopy analisys by Raman and mid-infrared
Keywords: Modificação de matrizes; Análise espectroscópica; Quimiometria; Modification of matrices; Spectroscopy analisys; Chemometrics; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA::METODOS OTICOS DE ANALISE